Reduction in Healthcare Resource Utilization Following Treatment With a Home-Based Footworn Device in Patients With Knee Osteoarthritis: A Retrospective Claims Analysis - Josh Mark; Shirley Shema-Shiratzky; Joel Sommer; Tim Nolan; Ganit Segal (Journal of Health Economics and Outcomes Research)
**Background:** One in 7 US adults has knee osteoarthritis (OA) and almost two-thirds of them suffer from low back pain. OA is the third most rapidly rising condition associated with disability and leads to a significant burden on the healthcare system and society. **Objective:** This study looked at the healthcare resource utilization (HCRU) in patients with knee OA and low back pain before and after the utilization of a new, home-based, noninvasive, biomechanical intervention. **Methods:** This was a retrospective claims analysis of 585 patients treated with a personalized, noninvasive, home-based, biomechanical treatment that aims to alleviate knee pain and improve function (AposHealth®). The date of the first AposHealth claim was the index date. Data prior to the index date and post-index date were used to monitor changes in HCRU while in treatment. Descriptive statistics, including frequencies, means and standard deviations, were used to present patient characteristics. To standardize the results, an average monthly claims data rate was calculated and an expected annual rate was extrapolated. Annual HCRU rate per 1000 members was calculated. **Results:** HCRU decreased after utilizing the new intervention including a decrease of 79% in diagnostic claims, a 70% decrease in outpatient services, a 22% decrease in non-operative treatments, a 61% decrease in pain medications including an 85% drop in opioids use, and a 44% decrease in intra-articular injections. The pre-index estimated rate for total knee replacement (TKR), which is based on existing literature, was 15.1%, whereas the post-index rate of TKR was 0.9%. **Conclusions:** Patients with knee OA treated with a home-based, noninvasive, biomechanical intervention incurred fewer healthcare resources, leading to an overall reduction in the cost of care.